Sodium Alginate- and Cationic Cellulose-Functionalized Polycaprolactone Nanofibers for In Vitro and Antibacterial Applications - Emad Tolba; Ahmed Salama; Ahmed K. Saleh; Iriczalli Cruz-Maya; Vincenzo Guarino (Molecules, 2023)
The use of polyelectrolytes is emerging as a fascinating strategy for the functionalization of biomedical membranes, due to their ability to enhance biological responses using the interaction effect of charged groups on multiple interface properties. Herein, two different polyelectrolytes were used to improve the antibacterial properties of polycaprolactone (PCL) nanofibers fabricated via electrospinning. First, a new cationic cellulose derivative, cellulose-bearing imidazolium tosylate (CIMD), was prepared via the nucleophilic substitution of the tosyl group using 1-methylimidazole, as confirmed by NMR analyses, and loaded into the PCL nanofibers. Secondly, sodium alginate (SA) was used to uniformly coat the fibers’ surface via self-assembly, as remarked through SEM-EDX analyses. Polyelectrolyte interactions between the CIMD and the SA, initially detected using a FTIR analysis, were confirmed via Z potential measurements: the formation of a CMID/SA complex promoted a substantial charge neutralization of the fibers’ surfaces with effects on the physical properties of the membrane in terms of water adsorption and in vitro degradation. Moreover, the presence of SA contributed to the in vitro response of human mesenchymal stem cells (hMSCs), as confirmed by a significant increase in the cells’ viability after 7 days in the case of the PCL/CMID/SA complex with respect to the PCL and PCL/CMID membranes. Contrariwise, SA did not nullify the antibacterial effect of CMID, as confirmed by the comparable resistance exhibited by S. mutans, S. aureus, and E. coli to the PCL/CIMD and PCL/CIMD/SA membranes. All the reported results corroborate the idea that the CIMD/SA functionalization of PCL nanofibers has a great potential for the fabrication of efficient antimicrobial membranes for wound healing.